Measuring the product quality of Malaysian herbal industry: a pilot study - Mazita, Mokhtar; Nor Hasnul Azirah, Abdul Hamid; Rozita, Mokhtar; Muhammad Aiman, Zulkifli (2021)
The herbal industry in Malaysia is a growing sector, driven by positive prospects and opportunities. This industry has contributed to national economics. It is projected that by 2020, Malaysia herbal industry worth will increase over RM 2 trillion compared to RM 777 billion in 2009 [1]. As reported by [2], Malaysians spent US$ 500 million annually on herbs, the Americans US$ 2700 million, Australian US$80 million, Canadian US$ 2400 and US$2300 is spent on herbs in the United Kingdom. Government interest in herbal industries in Malaysia has been translated into various initiatives such as the Third National Agriculture Policy 1998, National Policy on Traditional & Complementary Medicine 2000, Science & Technology Policy 2003, Biotechnology Policy 2004 and many more [2].